Analysis of Factors Influencing Clean and Healthy Behavior in Penjaskesrek Students at Musamus University, Merauke - Umakaapa, Muktamar (Tadulako University, 2023)
The application of a clean and healthy lifestyle (PHBS) is an effort to prevent individuals or communities from getting health problems. Cultivating PHBS awareness can be carried out in tertiary institutions as formal institutions that function to educate students. This study aims to determine the factors that influence the implementation of healthy and clean living in Penjaskesrek students at Musamus University. This research is an analytic survey research using a cross sectional approach. The number of samples in this study were 44 respondents. The sampling technique uses nonprobability sampling with total sampling technique. The data collection method uses a questionnaire distributed online to students. Data analysis using the SPSS application program. The results showed that the results of the study obtained factors that influenced PHBS of Physical Education, Health and Recreation students at Musamus University, including attitudes (P value 0.027 and OR 0.000), the role of lecturers (P value 0.085 and OR 4.200). It was concluded in this study that the most dominant factor in PHBS for Physical Education, Health and Recreation students at Musamus University was the role of the lecturer with a Prevalence Ratio (RP) value of 0.945. It is hoped that the Musamus University campus will be able to launch a PHBS program within Musamus University and provide support to students to carry out PHBS in the campus environment.